2021
DOI: 10.3390/vaccines9121449
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Perception, and Willingness towards Immunization among Bangladeshi Population during COVID-19 Vaccine Rolling Period

Abstract: Vaccine willingness among the mass populace, as well as their proper knowledge and perception regarding vaccines and the vaccination process, may contribute extensively towards attaining their anticipated vaccination rates. The current study endeavored to ascertain the Bangladeshi population’s knowledge, perception, and willingness towards COVID-19 vaccination. Relevant information was collected from 1201 adults aged 18 years or older by employing an online-based survey from 1 to 30 July 2021. Descriptive stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 44 publications
1
38
0
2
Order By: Relevance
“…Based on several pieces of evidence and data, some relevant hypotheses might be tested to sort out a strong relationship between the current study covariates [Gender: male, female, age: ≤ 20, 21–24, > 24 years; level of schooling: lower grade-1st/2nd/3rd year, higher grade-4th/5th/Master's or higher; current living area: urban, rural; family monthly income: <25,000 BDT, 25,000–50,000 BDT, > 50,000 BDT ( 22 , 31 ); university type: private, public, and others] with the outcome variables to establish the study objectives. In addition, fear of educational gap (yes, no), having job insecurity (yes, no), having online exam phobia (yes, no), and dissatisfaction toward e-Learning (yes, no) were considered as independent variables while measuring the degree of psychological distress among university students in Bangladesh.…”
Section: Methodsmentioning
confidence: 99%
“…Based on several pieces of evidence and data, some relevant hypotheses might be tested to sort out a strong relationship between the current study covariates [Gender: male, female, age: ≤ 20, 21–24, > 24 years; level of schooling: lower grade-1st/2nd/3rd year, higher grade-4th/5th/Master's or higher; current living area: urban, rural; family monthly income: <25,000 BDT, 25,000–50,000 BDT, > 50,000 BDT ( 22 , 31 ); university type: private, public, and others] with the outcome variables to establish the study objectives. In addition, fear of educational gap (yes, no), having job insecurity (yes, no), having online exam phobia (yes, no), and dissatisfaction toward e-Learning (yes, no) were considered as independent variables while measuring the degree of psychological distress among university students in Bangladesh.…”
Section: Methodsmentioning
confidence: 99%
“…In a study carried out in Australia to understand the perception towards future COVID-19 vaccination, the majority of the public held positive view [ 9 ]. A study in Bangladesh showed vaccine uptake was affected by inadequate knowledge and perception of respondents [ 10 ]. Nigeria and Ghana had just over 50% of the population studied as willing to take the vaccine and recommend it to others [ 11 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is no option but to increase the vaccination rate to combat the newly emerged Omicron variant. 13 , 14 , 15 Also, we recommend ensuring booster dose for the susceptible population as this additional dose gives an extra layer of protection. As the booster dose of the mRNA vaccine can reduce the complications related to COVID, it is necessary to ensure the booster shots as early as possible.…”
mentioning
confidence: 99%